Tunable electronic properties of monolayer silicane via fluorine doping: a first-principles study. (25th May 2017) - Wang, Jing; Duan, Xiangmei
Abstract: The electronic structures of fluorine-doped monolayer silicane (F-silicane) are investigated using the density functional theory. We find that the concentration of fluorine has an effect on the electronic properties such as surface work function and energy band structure. The band gap of F-silicane decreases monotonously as the covering percentage of F increases. With favorable formation energy, moderate band gap and appropriate work function, 50% F doped silicane is expected to be a potential candidate for water splitting reaction.